2008
DOI: 10.2119/2008-00079.parrish
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TNF Release by Choline Requires α7 Subunit Nicotinic Acetylcholine Receptor-Mediated Signaling

Abstract: The α7 subunit-containing nicotinic acetylcholine receptor (α7nAChR) is an essential component in the vagus nerve-based cholinergic anti-inflammatory pathway that regulates the levels of TNF, high mobility group box 1 (HMGB1), and other cytokines during inflammation. Choline is an essential nutrient, a cell membrane constituent, a precursor in the biosynthesis of acetylcholine, and a selective natural α7nAChR agonist. Here, we studied the anti-inflammatory potential of choline in murine endotoxemia and sepsis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
210
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(229 citation statements)
references
References 38 publications
16
210
0
3
Order By: Relevance
“…ACh, the vagal neurotransmitter, attenuated both the early and late phase of LPS-induced TNF-α release in human macrophages [29]. Activation of α7 nAChR attenuates LPS-induced acute lung injuries and improves the survival of mice with sepsis [30,31]. In contrast, vagus nerve stimulation in α7 nAChR-deficient mice failed to reduce serum TNF levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…ACh, the vagal neurotransmitter, attenuated both the early and late phase of LPS-induced TNF-α release in human macrophages [29]. Activation of α7 nAChR attenuates LPS-induced acute lung injuries and improves the survival of mice with sepsis [30,31]. In contrast, vagus nerve stimulation in α7 nAChR-deficient mice failed to reduce serum TNF levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…JXG is a non-Langerhans histiocytic infiltrate. The classic finding in JXG is the Touton cell , a multinucleated histiocyte with finely vacuolated, foamy cytoplasm [8,9,10]. The Touton cell is characteristic but not specific for JXG [11].…”
Section: Discussionmentioning
confidence: 99%
“…Well-developed xanthogranulomas have numerous foamy cells. However, early in the course of the lesion, these may be reduced in number or absent [9, 10, 12]. Histiologic specimens are generally reactive for factor XIII and macrophage markers, including Ki-M1P [9,10,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have demonstrated that the release modulation of TNF-α by inflammatory cells requires cholinergic signaling of α7nAChR [57], as well as NFκB signaling of the transduction of this cytokine [58]. There were high levels of TNF-α in VAG hamsters during the 7 days postinfection.…”
Section: Discussionmentioning
confidence: 99%